Tectonic History of the Arctic Basins: Partial Solutions and Unsolved Mysteries (Chapter 3) - Vogt,Peter R.; Avery,Otis E. (1974)
As yet inaccessible to deep-sea drilling and shipborne surveying, the ice-locked Arctic Basin has been slow to give up details of crustal genesis and later modification. Extensive geophysical surveying both in the Arctic Basin and the North Atlantic confirms sea-floor spreading as the only probable mode of crustal genesis for the Eurasia Basin. Magnetic anomalies, although less clear than elsewhere suggest spreading rates of approximately 0.5 to 1 cm/yr since 10 m.y.b.p.; the basin was born perhaps 60 m.y.b.p., with the separation of the Lomonosov Ridge from the Eurasian margin. Reprint from Marine Geology and Oceanography of the Arctic Seas.